Effects of dietary supplementation with fenugreek seeds, alone or in combination with probiotics, on gilthead seabream (Sparus aurata L.) skin mucosal immunity. Issue 65 (June 2017) - Guardiola, F.A.; Bahi, A.; Bakhrouf, A.; Esteban, M.A.
Abstract: Despite increasing interest in modulating the immune response of fish, providing a combination of probiotics and herbal immunostimulants in aquafeed has rarely has been studied. The effects on gilthead seabream ( Sparus aurata L.) of the dietary administration of fenugreek ( Trigonella foenum graecum ) seeds alone (FE), or combined with one of the following probiotic strains: Bacillus licheniformis (FEBL), Lactobacillus plantarum (FELP) or Bacillus subtilis (FEBS) were evaluated. Fish were fed a control or one of the supplemented diets for 3 weeks. After 2 and 3 weeks of the feeding trial, the abundance of terminal carbohydrates, IgM levels, enzymatic activities (proteases, alkaline phosphatase, esterase and ceruloplasmin) and bactericidal activity were determined in skin mucus. Our results demonstrated that the dietary administration of FE in combination with L. plantarum, particularly, increased carbohydrate abundance, the activity of certain enzymes such as ceruloplasmin, and bactericidal activity against the pathogenic bacterium Photobacterium damselae and the non-pathogenic bacterium B. subtilis in skin mucus at the end of the trial. The carbohydrates most affected by the FELP diet were mannose/glucose, N-acetyl-d -galactosamine and N-acetyl-β-d -glucosamine. Interestingly, IgM levels were significantly higher in fish fed the FELP and FEBS diets whilst protease activity generally increased in all supplemented diets, which could suggests that the main effect in this activity was to the result of FE supplementation although that fact cannot be confirmed because the effects of probiotics addition alone were not studied. These results suggest that the combined dietary administration of fenugreek and L. plantarum will best enhance the skin mucosal immunity response of gilthead seabream. Graphical abstract: Highlights: The combined use of probiotics and herbal immunostimulants has been rarely studied in fish. Skin mucosal immunity was enhanced mainly by fenugreek + L. plantarum diet (FELP). FELP diet significantly increased the carbohydrate abundance, some enzymes and the bactericidal activity of mucus. IgM levels were significantly higher in fish fed FELP and FEBS enriched diets. Protease activity in skin mucus was increased in all supplemented diets.